Calculating the carbon footprint: Implications for governing emissions and gender relations. Issue 2 (June 2016) - de Aguiar, Thereza R.S.; Fearfull, Anne; Sanagustín Fons, María V.
Highlights: Examination of a particular carbon calculator introduced by the British Government. Analysis of the Act on CO2 calculator as a gendered household accounting technology. Exploration of householders' accountability in attempts to reduce personal footprint. Analysis of footprint technologies as tools for changing householders' lifestyles. Abstract: In this article, we use fresh empirical evidence, and draw on feminist and critical accounting and organizational theories to contend that carbon calculators can be interpreted as discriminatory control technologies. They do this by providing a new and flexible vocabulary for governing expenses, costs and investments at a distance, avoiding a sense of direct intervention by the government. Thus, given our stance that the carbon calculator cannot be considered a neutral tool, we argue that it has the potential to control personal responsibilities regarding both environmental and family-based issues.